The study of the implementation and the efectiveness of O.S.H.A on construction site (A case study on Putrajaya Construction Site) / Mohammad Mubarak Basir Ahmad - Basir Ahmad, Mohammad Mubarak (2002)
This academic exercise is to give a clear understanding of the roles played by DOSH on a construction site. The aim to this study is to find out how efficient do the OSHA laws imposed by DOSH have on the construction site. Furthermore the study is carried out to identify any difficulty by DOSH in imposing all the OSHA laws on the construction site. The researcher gathered data by giving out questionnaires. The questionnaires were to seek DOSHs’ opinions concerning the effectiveness and the implementation of OSHA laws on construction site.The researcher used 50 personals and staff of DOSH of Putrajaya.